Tricycle Project – One Health approach: Whole genome sequencing(WGS) of Extended-spectrum beta-lactamase (ESBL) producing Eschericia (E.) coli derived from human, food chain and environment. (March 2022) - Hashim, R.; Husin, S. Amir; Ahmad, N.; Bahari, N.; Abu, N.; Ali, R. Mohd; Hashim, N.H.F.; Ramasamy, P.; Saberi, M.R. Hassan; Laine, L. Yee; Rashid, F. Abdul; Rasid, N.A. Abd; et al.
Abstract : Purpose: Antimicrobial resistance (AMR) phenomenon is a global health issue. The surging of resistant infections is pushing up costs of treatment, leading to difficulty in treating infections, worse clinical outcomes f and severe economic loss. AMR is not limited to human health. The problem also has impacts on animal husbandry practices resulting in similarly higher costs for treatment and animal-origin food production. Effort to address this requires a One Health-holistic and multisectoral approach, as resistant bacteria arising in humans, animals or the environment may spread from one to another leading to bigger threat. One-health approach pilot project was established as integrated surveillance system to monitor ESBL E.coli in three main areas of concern; human (hospital and community), food, and the environment based on a global protocol. The use of ESBL producing E coli as a single indicator for Gram-negative resistance was adopted from European Antimicrobial Resistance Surveillance Network. Methods & Materials: Ninety- eight ESBL producing E.coli were selected for whole genome analysis using Nextera® XT DNA Library Preparation kit (Illumina®, USA).Twenty-five isolated were derived from hospitalized patients, seven from community Health Clinics, 46 isolates were from chicken ceca samples representing food chain and 20 were from water samples. Results were analyze using Resfinder 3.2, Multi-Locus Sequence Typing 2.0 and CSI phylogeny 1.4. Results: The strains isolated were diverse with 51 different ST identified. ST45 (5/98 5%) was the predominant type, however ST3 was more widely distributed, detected among hospital strains and food chain sector. Nineteen new clones were identified. Single nucleotide polymorphism phylogenetic analysis of core genomes revealed that all organisms were interrelated. Majority of the isolates harbored ESBL blaCTX-M- 33 gene (n=76)(76%). In addition, some isolates also harbored carbapenemases resistant gene; blaOXA 1 (n=5)(5%), blaOXA2 (n=10)(10%) and colistin resistant gene; blaMCR1 (n=40)(40%) and blaMCR3 (n=4)(4%). Conclusion: Isolates derived from all three sources were interrelated. The concept of one-health approach is very important in understanding the spread as well as combating antimicrobial resistance.